Human platelets efficiently kill IgG-opsonized E. coli - Riaz, Anum H. (2012)
Platelets are known contributors of hemostasis but have recently been shown to be important in inflammation and infectious diseases. Moreover, thrombocytopenia is often observed in patients with sepsis. We previously reported that platelets actively phagocytosed IgG-coated latex beads. In the current study, the capacity of human platelets to participate in host defense against bacterial infections was determined by assessing their ability to kill E. coli. Washed human platelets were incubated with unopsonized or IgG-opsonized E. coli and evaluated for binding and killing of E. coli. We found that although both unopsonized and IgG-opsonized E. coli associated with platelets, only IgG-opsonized E. coli were efficiently killed unless platelets were activated by a potent agonist. The bactericidal activity was dependent on FcγRIIA, was sensitive to cytochalasin D, but was not due to reactive oxygen metabolites. These data suggest that platelets may play an important role in protection against infection.